THE ORETICAL AND METHODOLOGICAL ASPECTS OF SYSTEMATIC INVESTIGATION OF THE LOCAL ETHNIC COMMUNITIES IN MICROHISTORICAL REGION (BY THE EXAMPLE OF MYASNIKOVSKY DISTRICT OF ROSTOV REGION OF THE SECOND HALF OF THE XX CENTURY) - E. A. Hoshafyan (Гуманитарные и юридические исследования)
The present study examines the complex set of theoretical and methodological issues related to the system of regional study of the historical process. The main object of the research is the local ethnic community represented by the Armenian community of Myasnikovsky district of Rostov region and localized by spatial boundaries in microhistorical region. The main method employed in the study is qualitative synthesis of differentiated concepts which allow to develop an adequate descriptive model.